(untitled) (Jurnal Adabiya, 2020)
The tradition of deer hunting is an activity undertaken to catch deer using dog help, followed by many people and led by the handler. This paper is the result of a study that explores in depth the procession of deer hunting tradition, the meaning contained in deer hunting, and the public’s view of deer hunting activities in Kluet Tengah District. This research is a qualitative research and data collection technique is done through observation and interviews of key infomation which know about deer hunting tradition, such as deer handler, customary figures, adat leaders, community leaders, and experienced people and directly involved in the implementation deer hunting traditions, and literature studies. The results show that the hunting tradition is still frequently performed by the Kluet community, especially in the wake of the commemoration of the big days that will be carried out by the community. Hunting tradition also has taboos that must be obeyed by hunting members to avoid misfortune or misfortune. According to society’s perception, deer animals have guards in the form of spirits who have the power to wound anyone who harassed his home and animals. For this reason, before a hunting activity, the handler must perform several stages and ritual processes to ask not to be disturbed and given his animal. The process of burning keminjon, preparing tools, searching for perjak, seeking bekih, and profit sharing. The results of deer hunting are always shared with all the people present during the division process, although he did not participate in the hunt